Comparing the immune responses of two genetically B-complex disparate Fayoumi chicken lines to Eimeria tenella. Issue 2 (3rd March 2016) - Lee, S.-H.; Dong, X.; Lillehoj, H. S.; Lamont, S. J.; Suo, X.; Kim, D. K.; Lee, K.-W.; Hong, Y. H.
Abstract: The present study was conducted to compare the susceptibility of congenic Fayoumi lines to Eimeria tenella infection and to assess genetic differences in Eimeria egression. Chickens were orally inoculated with 5 × 10 4 sporulated E. tenella oocysts and challenged with 5 × 10 6 oocysts on the 10th day after the primary infection. The Fayoumi M5.1 line exhibited higher levels of body weight gain, less oocyst shedding and higher percentages of B and CD4 + /CD8 + T cells than the M15.2 chickens. These results demonstrate that M5.1 line is more resistant to E. tenella infection than M15.2 line. Furthermore, the percentage of sporozoite egress from peripheral blood mononuclear cells (PBMCs) was higher in the M5.1 line. The results of this study suggest that enhanced resistance of Fayoumi M5.1 to E. tenella infection may involve heightened cell-mediated and adaptive immunity, resulting in reduced intracellular development of Eimeria parasites.